(untitled) - Williams, David Brian (New York, 1996)
Contents: Experiencing Music Technology provides a comprechensive, systems approach to using and understanding computers and music. Rather than placing the main focus on timely commercial hardware and software concers, we consider broader issues of people, procedures, data, software, hardware, environment, and software development.
Keywords: Nhạc,Music; Xử lý dữ liệu,Data processing